Protect Android based system from Botnet - Ma, Jizhou (2016)
With the rapid development of mobile Internet today, smart mobile phone has become an important tool for people to communicate and acquiring the outside information. To some extent, smart mobile phone is equivalent to a small PC, which has 71.6% Android mobile phone users. The open source Android platform makes the number of mobile phone softwares increasing in the market. Some malicious softwares not only threaten the performance and security of mobile phone, but also lead to the loss of time and finance from weak consciousness of mobile phone users. As a consequence, mobile phones become one of the main cyber-criminal objects especially via an installation of package of mobile botnet. According to the existing problems in people's daily use of mobile phones, the whole project is based on the Android development platform, using Java language, abided by the Model-View-Controller (MVC) design pattern, equipping with SQLite embedded database, basically completing this practical botnet killer software. The application is mainly based on a new proposed theory to remove botnet and monitor malicious behaviors from botnet. The test result prove that the theory is reasonable, correct and stable. The software is mainly to achieve the functions that the botnet killer can protect android system from botnet. Keywords: Botnet; Android operation system; MVC design pattern; Botnet killer;